WISATA PERBATASAN (CROSS BORDER TOURISME) UNTUK KESEJAHTERAAN PENDUDUK LOKALDI KAMPUNG SOTA, DISTRIK SOTA, KABUPATEN MERAUKE - sebestina siman; hendricus Lembang (Musamus Journal of Economics Development, 2019)
Sota Village has an unique attraction as a cross border tourism between Indonesia and Papua New Guinea and has become the favorite destination in Merauke Regency. This study aims to find and prove the determinant factors of cross border tourism to improve the welfare of local residents in Sota Village, Sota District, Merauke Regency. The type of research used is a qualitative approach by expolarizing information on field data and literature so that data can describe the events that take place factually, systematically and accurately. The results of the study found that cross border tourism has made a positive contribution in supporting the regional economy, business sectors related to the tourism industry sector have increased income, distribution of basic needs, expansion of economies of scale. In addition, infrastructure and other supporting facilities, the community has felt the benefits such as the ease and smooth flow of human and goods mobilization. However, the indigenous people of the Kanum Tribe are still very limited and have not had much direct impact on their welfare. Because they are still very few who are directly involved in business activities related to tourism such as: food businesses, trade, even cultural arts, crafts and so on. Several causes are the quality of human resources is still low, lack of the spirit of entrepreneurship, awareness of the role of the tourism industry sector for economic life. So that the attention of the cultural values ​​and customs of the Kanum Tribe as a native population has not been widely appointed as one of the tourist advantages. Keywords: Border tourism, welfare, attention to cultural values